SOWING DEPTH AND LIGHT INTENSITY IN THE EMERGENCE AND DEVELOPMENT OF MONOCOTYLEDONOUS WEEDS - Marques, Ricardo Fagundes [UNESP]; Souza, Guilherme Sasso Ferreira [UNESP]; Pereira, Maria Renata Rocha; Marchi, Sidnei Roberto; Martins, Cibele Chalita [UNESP]; Martins, Dagoberto [UNESP] (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2022)
This study aimed to evaluate the effects of different sowing depths and light intensities on the emergence and development of the monocot weed species, Urochloa decumbens and Cenchrus echinatus, under field conditions. Each species constituted an experiment, and the experimental design was completely randomized with four replicates. The treatments were arranged in a 6 x 4 factorial scheme, with six sowing depths (0.5, 1.0, 2.0, 4.0, 8.0, and 12.0 cm) associated with four solar radiation intensities (100%, 70%, 50%, and 30%) obtained through the use of shading screens. Seedling emergence capacity was evaluated daily to obtain the emergence percentage and speed index. Plant height, floral induction time, and plant dry matter at flowering were measured. Even when subjected to different solar radiation intensities, U. decumbens and C. echinatus seedlings emerged at all the sowing depths. Sowing between 2.0-and 4.0-cm depths favored the emergence of seedlings of U. decumbens and C. echinatus. However, sowing at 12-cm depth reduced the emergence of both species regardless of the solar radiation intensity. Urichloa decumbens plants grown under conditions of greater shading showed the lowest values of height and dry matter accumulation during flowering. High levels of shading facilitated only the etiolation of C. echinatus plants. Increased shading flowering time in both species compared to full sunlight.
Keywords: Brightness; Cenchrus echinatus; Field condition; Shading; Urochloa decumbens